Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Kemampuan Menulis Buku Harian Siswa Kelas V SD Katolik Wanno Baru - Kenda, Ristoyanus Umbu; Lende, Petrus; Lede, Yohanes Umbu (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to produce the writing of diaries by fifth-grade students of SD Katolik Wanno Baru using the Project Based Learning model. This study uses the classroom action research method and is carried out in 2 cycles, each consisting of four main activity stages, namely: Planning, Acting, Observing, and Reflecting. The subjects of this study are fifth-grade students of SD Katolik Wanno Baru totaling 30 students. The data analysis was conducted after the learning process was completed, with the learning outcomes of each cycle represented by the scores obtained by the students. To calculate the students' learning mastery and learning outcomes in grade V at SD Katolik Wanno Baru for the Indonesian subject on the topic of diaries, in cycle I it was still considered low. This is evident from the test results, where 11 students achieved mastery and 19 students did not, with an average score of 36.6%. In cycle II, there was a change, namely an improvement, as seen in the learning outcomes where 25 students achieved mastery and 5 students did not, with an average score of 83.3%. Thus, it can be concluded that the use of the Project Based Learning model is effective in improving the diary-writing skills of grade V students at SD Katolik Wanno Baru